2015
DOI: 10.12968/ajmw.2015.9.2.66
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the infant feeding choices of HIV-positive mothers at a level two hospital in Cape Town

Abstract: Background/Aims: Following the decision by the South African Department of Health in 2012 to withdraw the provision of free infant formula milk to HIV-exposed infants, policy makers have grappled with the need to develop guidelines to help HIV-positive mothers decide whether they should breastfeed their babies. The objectives of this study were to assess the infant feeding choices of HIV-positive mothers and to determine factors influencing their behaviours prior to the process of withdrawing the provision of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Almost a third of studies (18 of 56, 32.1%) reported policy-related barriers [ 30 – 32 , 34 , 35 , 38 50 ] while 20 studies (35.7%) described facilitators [ 30 , 31 , 33 – 35 , 37 , 39 43 , 47 , 50 56 ]. Poor leadership and management structures were described as barriers to effective facility-based breastfeeding [ 30 , 40 , 47 , 50 ], such as when hospital management felt that BFHI was extra work to implement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Almost a third of studies (18 of 56, 32.1%) reported policy-related barriers [ 30 – 32 , 34 , 35 , 38 50 ] while 20 studies (35.7%) described facilitators [ 30 , 31 , 33 – 35 , 37 , 39 43 , 47 , 50 56 ]. Poor leadership and management structures were described as barriers to effective facility-based breastfeeding [ 30 , 40 , 47 , 50 ], such as when hospital management felt that BFHI was extra work to implement.…”
Section: Resultsmentioning
confidence: 99%
“…Poor leadership and management structures were described as barriers to effective facility-based breastfeeding [ 30 , 40 , 47 , 50 ], such as when hospital management felt that BFHI was extra work to implement. Also frequently reported was limited implementation of breastfeeding policies [ 34 , 35 , 39 , 41 , 43 , 45 50 , 57 ], particularly at peripheral health facilities. For example, a study in Ghana found that although almost all policy makers and implementers were aware of the national breastfeeding policy, there was a lack of written guidelines and posters at peripheral health facilities because materials were passed from national to regional, district and then health facilities with bureaucracy and transport barriers encountered between each level [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing the rate of exclusive breastfeeding (EBF) in the first six months of life to 50% is one of six major global targets set by the United Nations (UN) Decade of Nutrition [ 1 ], and improving exclusive and sustained breastfeeding rates is essential for achieving sustainable development goals (SDGs) to eradicate hunger and end malnutrition by 2030 [ 2 ]. If implemented globally at near universal levels (> 90%), optimal breastfeeding practices could reduce global child deaths by more than 800,000 [ 3 ], which makes breastfeeding the most effective preventive intervention to improve infant mortality [ 4 ].…”
Section: Introductionmentioning
confidence: 99%